673. Syphilis Outbreak in Women Who Have Sex with Men in Japan: A Case–Control Study in Tokyo, 2017–2018. (26th November 2018) - Nishiki, Shingo; Arima, Yuzo; Yamagishi, Takuya; Hamada, Takashi; Takahashi, Takuri; Sunagawa, Tomimasa; Matsui, Tamano; Oishi, Kazunori; Ohnishi, Makoto
Abstract: Background: In Japan, syphilis notifications have increased sharply, with Tokyo accounting for a third of all cases. Importantly, the increase in women has been remarkable, with the majority being women who have sex with men. We therefore conducted a prospective case–control study to evaluate correlates of recent syphilis infection among women in Tokyo. Methods: We employed a test-negative design case–control study among women who sought a syphilis test at a women's health clinic in Tokyo, comparing socioeconomic status, medical history, and recent sexual behaviors/partnerships, between those who were diagnosed with recent syphilis infection based on clinical signs and serological test results (cases) vs. those who were nonreactive for the nontreponemal test (controls). Participants aged ≥20 years and sexually active in the past 6 months were recruited from June 2017 to March 2018 and completed a self-administered questionnaire. We described cases and assessed for correlates of recent syphilis infection based on odds ratios (ORs) and 95% confidence intervals (CIs). Results: A total of 524 women, composed of 60 cases and 464 controls, were enrolled. The median age was 23 years (range = 20–54) among cases and 26 years (range = 20–59) among controls. Of the 60 cases, 10 (17%) were current students and three (5%) had a history of syphilis; in the past 6 months, while 35 (58%) had engaged in commercial exchange of sexual practices, 14 (23%) had only one sex partner. Having lower educational attainment (OR = 4.1; 95% CI = 2.1–8.1), not being employed full-time (OR = 3.1; 95% CI = 1.8–5.5), and commercial exchange of sexual practices (OR = 3.4; 95% CI = 2.0–5.9) were associated with case status in univariate analysis. The association between case status and inconsistent condom use (relative to consistent condom use) during vaginal/anal sex in the past 6 months (OR = 2.0; 95% CI = 0.9–4.3) became stronger when restricted to women engaged in commercial exchange of sexual practices (OR = 4.0; 95% CI = 1.4–10.9). Conclusion: This was the first study to evaluate potential risk factors for recent syphilis infection among women in Japan. In light of these findings, we may need a multi-pronged approach to prevent and control syphilis, for both those engaged in commercial exchange of sexual practices and the general population. Disclosures: All authors: No reported disclosures.